RONCUS TURRESI: A NEW CAVE-DWELLING PSEUDOSCORPION SPECIES FROM SOUTHEASTERN SERBIA (NEOBISIIDAE, PSEUDOSCORPIONES) (Acta Entomologica Serbica, 2021)
A new cave-dwelling pseudoscorpion species belonging to the genus Roncus L. Koch, 1873, Roncus turresi sp. n., from southeastern Serbia (a small unnamed cave up to Vladikine Ploče Cave, near the town of Pirot) is established in the present paper. Its main morphological characters and diagnostic features are analyzed, illustrated and compared with its closest congeners from southeastern Serbia. This new cavernicolous pseudoscorpion is endemic to a small area of Mt. Stara Planina in southeastern Serbia.